Haunted houses : classic stories of doors that should never be opened - Landis, John, 1950-; James, Henry, 1843-1916; Poe, Edgar Allan, 1809-1849; Lytton, Edward Bulwer, baron, 1803-1873; Blackwood, Algernon; Wells, H. G. (Herbert George), 1866-1946; Lovecraft, H. P. (Howard Phillips), 1890-1937; Bierce, Ambrose, 1842-1914?; Wilde, Oscar, 1854-1900; Landon, Perceval; Stoker, Bram, 1847-1912; Gilman, Charlotte Perkins, 1860-1935; et al. (The library of horror., 2020)
Classic haunted house ghost stories curated by world-renowned filmmaker and horror genre expert John Landis. This beautifully presented, highly collectible anthology features ghost stories that have enthralled, terrified and inspired readers decade after decade. Some are relatively well known; others are long-lost treasures, awaiting rediscovery. The selection includes tales of terror by Bram Stoker, H. P. Lovecraft, and Percival Landon; studies of creeping dread by Edgar Allan Poe and Henry James; short, sharp shockers by Ambrose Bierce, M.R. James and Lafcadio Hearn; and comedic masterpieces by Oscar Wilde and Saki. Mr. Landis' own introduction explores each tale's fascinating impact on the contemporary horror genre. Step inside these ghost-ridden repositories of supernatural evil, if you dare...